2022
DOI: 10.3389/fpls.2022.840614
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Genome Wide Association Studies Reveal Rich Genetic Architectures of Grain Zinc and Iron in Common Wheat (Triticum aestivum L.)

Abstract: Biofortification is a sustainable strategy to alleviate micronutrient deficiency in humans. It is necessary to improve grain zinc (GZnC) and iron concentrations (GFeC) in wheat based on genetic knowledge. However, the precise dissection of the genetic architecture underlying GZnC and GFeC remains challenging. In this study, high-resolution genome-wide association studies were conducted for GZnC and GFeC by three different models using 166 wheat cultivars and 373,106 polymorphic markers from the wheat 660K and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Yield-related traits are complex quantitative traits controlled by polygenes [9][10][11], which are strongly influenced by genotypic and environmental factors [12]. In the last two decades, a large number of QTLs underlying wheat kernel size-related traits have been successfully identified by traditional bi-parental linkage mapping [7,[9][10][11][13][14][15][16][17]] and genome-wide association studies (GWAS) [18][19][20][21][22][23]. However, due to the large and highly repetitive nature of the wheat genome, identifying stable and robust QTLs for kernel size-related and yield traits remains challenging in wheat breeding [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Yield-related traits are complex quantitative traits controlled by polygenes [9][10][11], which are strongly influenced by genotypic and environmental factors [12]. In the last two decades, a large number of QTLs underlying wheat kernel size-related traits have been successfully identified by traditional bi-parental linkage mapping [7,[9][10][11][13][14][15][16][17]] and genome-wide association studies (GWAS) [18][19][20][21][22][23]. However, due to the large and highly repetitive nature of the wheat genome, identifying stable and robust QTLs for kernel size-related and yield traits remains challenging in wheat breeding [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…On chromosome 7B, GZnC associated QTL/markers, (i) QGZn.cimmyt-7B_1P2 between 485838522 and 506414028 bps (Crespo-Herrera et al, 2017) was flanked by the GZnC associated markers 7B_393314447 and 7B_516450006; (ii) QGZn.cimmyt-7B_1P1 (Crespo-Herrera et al, 2017) was in the same position as the GZnC and GFeC associated markers 7B_121570273 and 7B_126740591; (iii) QGZn.cimmyt-7B_2P1 (Crespo-Herrera et al, 2017) was in the same position as the GFeC associated markers 7B_131374909 and 7B_168075214 that were in high LD (D = 0.97); (iv) Tdurum_contig65979_289 (539220004 bps), a stable GZnC associated marker (Tong et al, 2022) was only 0.65 Mbps away from GZnC associated marker 7B_530585647 that was significant in this study. In addition, GZnC associated markers reported by Wang et al (2021) GZnC between 182142433 bps and 190801271 bps were flanked by the GFeC associated markers 7B_168075214 and 7B_196275863 that were significant in this study and constituted an LD block (D = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Given that only a few genome-wide association studies for GZnC and GFeC in bread wheat have been reported ( Guttieri et al, 2015 ; Alomari et al, 2018 ; Bhatta et al, 2018 ; Velu et al, 2018 ; Tong et al, 2022 ), our primary objective was to perform genome-wide association mapping for GZnC and GFeC using a large panel of 5,585 elite breeding lines from CIMMYT’s bread wheat (referred to as BW) improvement program and zinc (referred to as ZN) improvement program. The BW improvement program mainly focuses on developing high-yielding varieties along with stress-resilience, whereas the ZN improvement program focuses on developing high GZnC varieties along with high grain yield, high GFeC, and stress-resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed for the loci underlying grain number (H#AM), AX_108852477 (2A, 739.44 Mb), AX_94447339 (2B, 745.51 Mb) and AX_109276516 (2D, 625.03 Mb). If any loci are validated in other mapping populations, the roles of all three loci could be presumed (Tong et al, 2022). The associated loci identified in this study provide genetic basis for further elucidating the mechanisms of grain‐related traits.…”
Section: Discussionmentioning
confidence: 99%